effects of soft-segment molecular weight and organic modifier on properties of organic-modified MMT-PU nanocomposites - Wang, Chia-Hao; Shieh, Yeong-Tarng; Nutt, Steven (Journal of applied polymer science, 2009)
The effects of soft-segment molecular weight and organic modification of montmorillonite (MMT) on thermal and mechanical properties of segmented polyurethane (PU) elastomers were investigated. The PU/MMT nanocomposites were prepared by in situ polymerization, and the compositions included soft segments with number average molecular weights of 1000, 2000, and 2900, and organic-modified MMT (including MMT-30B and MMT-I30E). The nanocomposites produced were characterized using wide-angle X-ray diffraction (WAXD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and mechanical testing. The TEM and XRD results revealed that both MMT-30B and MMT-I30E were intercalated, and partially exfoliated by the PU. Mechanical tests showed that the PU1000 series in soft-segment molecular weight yielded superior tensile properties compared with the PU2000 and PU2900 series. Also, for a given molecular weight of soft segment in PU, the MMT-30B nanocomposites exhibited greater increases in Young's modulus, tensile strength, and elongation at break than the MMT-I30E counterpart, and the crystallinity of PU was enhanced by the clays.